Pre-Service Teachers' Understanding on Designing English Learning Materials Using Portfolio - Ismail, Nyak Mutia; Moriyati, Moriyati (SAGA: Journal of English Language Teaching and Applied Linguistics, 2025)
The success of the teaching and learning process depends mainly on well-designed and efficient resources. Thus, teachers' ability to design suitable and effective learning materials is pivotal in making the process successful. Even before becoming real teachers, they are compulsorily responsible for understanding material design. This study aimed to assess the participants’ understanding of designing earning materials using the portfolio assessment as a component of the learning process. Through the qualitative approach, 13 participants were involved. They are students—preservice teachers—who are still studying at the English Department, Universitas Serambi Mekkah, Aceh, Indonesia. The instruments used were initial interviews, questionnaires, and triangulation interviews to enhance the primary data. In data collection, participants were asked interview questions to assess their understanding and perception of suitable instructional materials. They had 15 minutes to complete questionnaires and were interviewed again for 10 minutes. The data analysis then went on using interactive analysis. The results show that, on average, 11 out of 13 participants did not understand designing good learning materials. Then, regarding their agreement on the effectiveness of the portfolio, they mostly agree on this statement. In conclusion, portfolio assessment is worth trying to enhance the preservice ability in designing good and effective learning materials for language teaching and learning.